Ian Donald-pioneer of obstetric ultrasound - Prema D'Cunha (Wolters Kluwer Medknow Publications, 2014)
The ultrasound has become quite commonplace in Obstetrics and Gynaecology.Its advent is however of fairly recent origin. It was pioneered in the late 1950s but has seen a meteoric rise to become the most important discovery of the twentieth century. It was the vision, eloquence and persistence of one man from Glasgow that saw its birth and widespread use. The man was Professor Ian Donald. This is his story, his dream.